2016
DOI: 10.3823/2236
|View full text |Cite
|
Sign up to set email alerts
|

Employment Of People With Disabilities In Romania

Abstract: Background: Promoting optimal social integration of people with disabilities, as active citizens, represents a major objective of Romanian health, social and political strategies.Methods: This paper represents a selective review of the statistic official information, published in 2015, by the National Authority for People with Disabilities (NAPD) and Ministry of Labor, Family, Social Assistance and Elderly (MLFSPEP). It represents an integrative approach, regarding the legislative and socio-economic framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous empirical studies suggest that other factors than demographics and injury-related variables, such as differences in the environment or psychological resources that have not been accounted for in this study, may explain a variation in labor market participation (LMP) of persons with disabilities [18]. As an international approach, in Article 27 of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) it is stated that it: "Recognizes the right of persons with disabilities to work, on an equal basis with others; this includes the opportunity to gain a living by work freely chosen or accepted in a labor market and work environment that is open, inclusive and accessible to persons with disabilities" [19].Due to the expected decline in the working-age population, particularly in the case of European countries, people with disabilities are perceived more and more frequently as a valuable resource in the labor force [20]. Previous empirical research studies on labor market integration and equality for people with disabilities in the case of Nordic and Baltic countries, i.e., Denmark, Sweden, Norway, Estonia, Latvia, Lithuania which are all members states of the European Union as well as Romania, suggested that national policies make a difference, that nondiscrimination policies are not enough and that a focused mix of regulatory and redistributive measures is appropriate to be implemented [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous empirical studies suggest that other factors than demographics and injury-related variables, such as differences in the environment or psychological resources that have not been accounted for in this study, may explain a variation in labor market participation (LMP) of persons with disabilities [18]. As an international approach, in Article 27 of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) it is stated that it: "Recognizes the right of persons with disabilities to work, on an equal basis with others; this includes the opportunity to gain a living by work freely chosen or accepted in a labor market and work environment that is open, inclusive and accessible to persons with disabilities" [19].Due to the expected decline in the working-age population, particularly in the case of European countries, people with disabilities are perceived more and more frequently as a valuable resource in the labor force [20]. Previous empirical research studies on labor market integration and equality for people with disabilities in the case of Nordic and Baltic countries, i.e., Denmark, Sweden, Norway, Estonia, Latvia, Lithuania which are all members states of the European Union as well as Romania, suggested that national policies make a difference, that nondiscrimination policies are not enough and that a focused mix of regulatory and redistributive measures is appropriate to be implemented [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ad laborem outcome was reserved, due to the external barriers in the community, represented by the nature of her job (military personnel), the distance and transport problems (the subject lives in Ilfov district, and she has neither driving licence, nor an adapted car) [13], [14].…”
Section: Case Reportmentioning
confidence: 99%
“…In Romania, the share of people with disabilities employed, compared to developed European countries (Norway 61.7%; Switzerland 62.0%; Austria 41.9%; Germany 46.1%; United Kingdom 38.9%) or North American ones (Canada 56.3%; USA 38.1%) was quite low at that time. (Anghelescu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%